1998
DOI: 10.1016/s0022-5223(98)70395-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ischemia-reperfusion injury of transplanted lung and the up-regulation of major histocompatibility complex II on host peripheral

Abstract: These results suggest that the intensity of the host immunogenic response is related to the severity of ischemia-reperfusion injury and is independent of tissue incompatibility and/or the type of ischemic insult. We conclude that the extension of ex vivo preservation time may predispose the transplanted lung to more severe rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…33,40 Prolonging pulmonary ischemia was also associated with higher MHC class II molecules expression by lung tissue, 32 a higher expression of human leukocyte antigen (HLA)-DR-b, 41 lower adenine nucleotide (TAN) levels, 33 and lower lung superoxide dismutase levels. 41 In addition, in the rodent IR model, significantly higher percentages of pulmonary cell necrosis were observed following increasing cold (4°C) ischemic times of beyond 12 h. 42 Furthermore, the percentage of necrotic cells was inversely correlated with the post-transplant graft function. 42 …”
Section: Ischemic Insultmentioning
confidence: 99%
“…33,40 Prolonging pulmonary ischemia was also associated with higher MHC class II molecules expression by lung tissue, 32 a higher expression of human leukocyte antigen (HLA)-DR-b, 41 lower adenine nucleotide (TAN) levels, 33 and lower lung superoxide dismutase levels. 41 In addition, in the rodent IR model, significantly higher percentages of pulmonary cell necrosis were observed following increasing cold (4°C) ischemic times of beyond 12 h. 42 Furthermore, the percentage of necrotic cells was inversely correlated with the post-transplant graft function. 42 …”
Section: Ischemic Insultmentioning
confidence: 99%
“…However, in a significant proportion of patients, severe reperfusion injury still leads to poor early graft function, 1,2 increasing the incidence of acute rejection, chronic graft dysfunction and postoperative mortality. 1,2,3,4 Mild to severe reperfusion injury is the second most frequent cause of death during the first 90 days after transplantation. 2 The mechanisms leading to lung reperfusion injury are complex and have not been fully comprehended.…”
mentioning
confidence: 99%
“…For instance, Qayumi et al found that greater than 2 hours of ischemia can predispose allografts to increased rates of graft rejection. 33 To minimize the warm ischemia period, the Cleveland Clinic protocol, for example, attempts to procure the hands and/or face before solid organ recovery. 3 However, an attempt to harvest 2 or 3 separate alloflaps seems quite challenging when one's goal is to prevent unnecessary donor instability.…”
Section: Donor-related Considerationsmentioning
confidence: 99%